Levels of anti-insulin antibodies in diabetic retinopathy patients: an observational cross-sectional study - Bismark N Mohammed; Emmanuel K Ofori; Christian N Adekena; Seth K Amponsah; Henry Asare-Anane; Seth D Amanquah; Mubarak Abdul-Rahman; Kwesi N Amissah-Arthur (Future Science OA)
Aim: This study evaluated the levels of anti-insulin antibodies (AIAs) and the influence of some antidiabetic medications on AIA in diabetes mellitus (DM) patients with retinopathy. Patient & methods: An observational cross-sectional study. Results: A lower titer of AIA IgG was observed in the diabetic retinopathy (DR) and DM-only study categories compared with the control group [DR = 86 (5–560), DM-only = 50 (5–500), versus control = 200 (7–565); p = 0.017]. Taking nifedipine and metformin were negatively correlated (r = -0.32, p = 0.04) with the levels of AIA IgE in the DR group. Conclusion: A decreased titer of circulating AIAs was observed in the DR study category, suggesting that AIA may not contribute to the pathogenesis of DR.